Crisis in the system of international relations and the new world order: the Chinese age - Д., Жекенов; С., Джакубаева; М., Азнабакиева (Journal of Oriental Studies, 2020)
The article is dedicated to determine the new challenges in the context of crisis in international relations system and to find out the new world order. According to the opinion of researchers the strengthening of one powerful state leads to the retreating of another. But this process is necessarily regulated by political, economic and even military conflicts, as a result, a new world order will be established and its leader will be determined. But COVID-19 offers a new scenario that no one expected. Of course, there are those who say that the coronavirus pandemic is a war, a biological war. However, this view still has no scientific basis. That is, the legitimacy of the above-mentioned world order is violated. It is not surprisingly that in the aftermath of the pandemic there will be many changes in the world order. But who will be the new leader of the new world order? There are a lot of predictions to that question, but one fact is clear, there is no country, that can win this fight on its own. This virus doesn’t spare anyone, all states must work together to win this epidemic. The principle of objectivity in the study of the current economic crisis in international relations, the systematic approach to the study of international relations as a theoretical and methodological basis, the historical-analytical method aimed at studying the foreign policy and economic relations of states, the diversity of data and information required the use of sorting methods. Key words: New World Order, World Crisis, COVID-19, People’s Republic of China, West-East Competition.